Non-Alcoholic Fatty Liver Disease and other Non-Communicable Diseases: Time for an Integrated Approach - Rastogi, Aayushi; Prasad, Manya; Ramalingam, Archana; Kapil, Umesh (Indian Journal of Community Health, 2022)
Non-Alcoholic fatty liver disease (NAFLD) is a broad term covering a spectrum of conditions ranging from hepatic steatosis, steatohepatitis and cirrhosis. NAFLD is highly prevalent across all regions of the world with its global prevalence of 25.2%(95%CI:22.1-28.7). It is commonly referred as the ‘hepatic manifestation’ of metabolic syndrome (MetS). Moreover, it is strongly associated with the individual components as well as MetS as a whole. NAFLD has been independently associated with other non-communicable diseases (NCDs) like chronic kidney disease (CKD), Polycystic ovary Syndrome (PCOS), Stroke and Cancers. This strong association of NCDs with NAFLD not only affects the prevalence but also the progression and management of the disease. Thus, this review aims at highlighting the association of NAFLD with other NCDs. A literature search was undertaken in the MEDLINE database using the necessary MeSH terms. The review concludes NAFLD is a systemic disease, not just confined to liver-specific morbidity and mortality, but also associated with numerous extra-hepatic manifestations, such as metabolic syndrome, cardiovascular diseases, chronic renal diseases, and malignancy. With co-existence of NAFLD with various NCDs it is expected to become the most overwhelming liver disease in the world in coming years. Hence, to reduce medical and economic impact associated with these comorbidities, it is recommended that all countries should estimate and predict the burden on comorbidities associated with NAFLD and galvanize its health resources in providing integrated therapeutic approaches for management of NAFLD and related comorbidities at an early stage.